Emotions and War
X, 274 p.
Keywords: This volume addresses the place of the emotions in literary representations of war across six centuries of European history. It challenges modern assumptions about the passions and feelings attending violent conflict in order to reveal the multifarious historical emotions and emotional histories of war.